Pengembangan Lembar Kerja Peserta Didik Berbasis Interaktif pada Pembelajaran Matematika Kelas V di Madrasah Ibtidaiyah Ad’dawah - Ria Setia listi; Endang Mulia Kurnianti (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
This study aims to develop an interactive-based Student Worksheet (LKPD) using a live worksheet. Mathematics subject, volume material on cubes and blocks for fifth grade elementary school. The type of research used is research and development (Research and Development) or called R&D. The research model used is ADDIE (Analysis, Design, Development, Implementation, Evaluations), the research consists of 5 stages. The subjects in the study were 15 students in the VC class. The instruments used are expert validation assessment questionnaires (materials, media, language), preliminary interview study sheets for teachers and students as well as teacher and student response questionnaires. Data collection techniques used in the form of teacher interviews, observation of learning activities and questionnaires. The results of the validation of the assessment of the LKPD were 82.35% material experts, 93% media experts and 80% linguists. The accumulation of the three experts obtained a percentage of 85%, which can be categorized as